Dinâmica das transições quiral e de desconfinamento da cromodinâmica quântica com o modelo Polyakov-Nambu-Jona-Lasinio - Peixoto, Thiago Carvalho [UNESP] (2014)
Thermodynamic equilibrium and non-equilibrium properties of the light u and d quarks sector of Quantum Chromodynamics (QCD) are studied with the Polyakov–Nambu–Jona-Lasinio (PNJL) model. The PNJL model allows to take into account simultaneously the chiral and deconfinement transitions at finite temperatures. The gran potential of the model is obtained in the mean field approximation. The gap equations for the order parameters that characterise these transitions, the quark condensate and the Polyakov loop, are solved numerically for different temperatures and the nature of the associated phase transitions is determined. Next, the Ginzburg-Landau-Langevin (GLL) equations that describe the temporal dynamics of the order parameters are obtained. The time scales involved in the thermalization of the quark condensate and Polyakov loop after a temperature quench are investigated as functions of the QCD Onsager parameters available in the literature. The relevance of the results obtained in the present dissertation for experiments of heavy ions collisions at high energies are discussed